2017
DOI: 10.1093/cid/cix724
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the US Maternal Tetanus, Diphtheria, and Acellular Pertussis Vaccination Program on Preventing Pertussis in Infants <2 Months of Age: A Case-Control Evaluation

Abstract: Background Infants aged <1 year are at highest risk for pertussis-related morbidity and mortality. In 2012, Tdap (tetanus toxoid, reduced diphtheria toxoid and acellular pertussis) vaccine was recommended for women during each pregnancy to protect infants in the first months of life; data on effectiveness of this strategy are currently limited. Methods We conducted a case-control evaluation among pertussis cases <2 months old with cough onset between January 1, 2011 and December 31, 2014 from six U.S. Emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 35 publications
2
93
2
3
Order By: Relevance
“…Observational studies indicate that pertussis vaccination in the third trimester reduced infection, hospitalisation, and mortality in infants compared with no vaccination in pregnancy 7475767778. A large British retrospective cohort study using primary care data demonstrated that the benefit of passive maternal immunity did not persist beyond the third dose of primary immunisation in the infant 79.…”
Section: How Can It Be Prevented?mentioning
confidence: 99%
“…Observational studies indicate that pertussis vaccination in the third trimester reduced infection, hospitalisation, and mortality in infants compared with no vaccination in pregnancy 7475767778. A large British retrospective cohort study using primary care data demonstrated that the benefit of passive maternal immunity did not persist beyond the third dose of primary immunisation in the infant 79.…”
Section: How Can It Be Prevented?mentioning
confidence: 99%
“…Maternal immunization during pregnancy, taking advantage of transplacental transfer of pertussis antibodies [1,3,12], was proposed to indirectly protect neonates against pertussis. This strategy achieves high pertussis antibody concentrations in infants [13], and is 64-93% effective in preventing disease among infants aged \ 2 months [14][15][16][17][18][19][20][21]. Moreover, breakthrough disease among infants whose mothers were vaccinated during pregnancy was less severe than those born to unvaccinated mothers [22].…”
Section: Introductionmentioning
confidence: 99%
“…50 More recently a study from the USA demonstrated that aP vaccination during the third trimester of pregnancy had a vaccine effectiveness of 78% (95% CI: 48–90%) against pertussis cases with cough in the <2 months age-group and a 91% (95% CI: 65%-97%) effectiveness against hospitalized cases. 51 Furthermore, a retrospective cohort study noted that infants with confirmed pertussis born to women vaccinated during pregnancy with aP vaccine were less likely to be hospitalized than cases born to women not vaccinated during pregnancy. 52 …”
Section: Maternal Pertussis Vaccinationmentioning
confidence: 99%